2003
DOI: 10.1016/s0010-2180(02)00458-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct observations of reaction zone structure in propagating detonations

Abstract: We report experimental observations of the reaction zone structure of self-sustaining, cellular detonations propagating near the Chapman-Jouguet state in hydrogenoxygen-argon/nitrogen mixtures. Two-dimensional cross sections perpendicular to the propagation direction were imaged using the technique of planar laser induced fluorescence (PLIF) and in some cases, compared to simultaneously acquired schlieren images. Images are obtained which clearly show the nature of the disturbances in an intermediate chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(99 citation statements)
references
References 34 publications
10
88
0
1
Order By: Relevance
“…When the hot jet is shut down, the contractive passway produced by the hot jet vanishes gradually. As shown in Fig.10, the slopes of the two curves both decrease after the shutdown of the hot jet, Fig.11, and the detonation structures are quite similar to the experimental images of CJ detonation for H 2 /O 2 /Ar mixture presented by Pintgen et al (Pintgen et al, 2003) As shown in Fig.12, when the hot jet is injected into the channel again at 900 μs t  , the CJ detonation changes to overdriven detonation once again because of reformation of the contractive passway. It is indicated that the newly formed overdriven detonation in stage D has almost the same overdrive degree as stage A, because the same contractive passway is generated in the flowfield after the re-injection of the same hot jet.…”
Section: Application Of Contractive Passwaysupporting
confidence: 75%
“…When the hot jet is shut down, the contractive passway produced by the hot jet vanishes gradually. As shown in Fig.10, the slopes of the two curves both decrease after the shutdown of the hot jet, Fig.11, and the detonation structures are quite similar to the experimental images of CJ detonation for H 2 /O 2 /Ar mixture presented by Pintgen et al (Pintgen et al, 2003) As shown in Fig.12, when the hot jet is injected into the channel again at 900 μs t  , the CJ detonation changes to overdriven detonation once again because of reformation of the contractive passway. It is indicated that the newly formed overdriven detonation in stage D has almost the same overdrive degree as stage A, because the same contractive passway is generated in the flowfield after the re-injection of the same hot jet.…”
Section: Application Of Contractive Passwaysupporting
confidence: 75%
“…Therefore, in this work L ≅ 50 HRL was chosen for a mixture with E a ∕RT o 20. Table 1 shows the thermophysical properties of the mixture considered in the present work also used in other investigations (e.g., [16,46,47] [15,[54][55][56]. The activation energy corresponds to the mixtures such as hydrogen-oxygen, acetylene-oxygen, and methane-oxygen at low pressures (see [7,10,15,54,[57][58][59]).…”
Section: Boundary and Initial Conditions And Grid Resolutionmentioning
confidence: 98%
“…Previous investigations indicate that the large-scale characteristics of a KH instability are visible when the shear layer is highly unstable [33] and the effect of viscosity and diffusion on the large-scale 12 characteristics of a RM instability is negligible [34]. It may be concluded that diffusion effect can easily suppress the small-scale vortices produced by KH instability, but only play a minimal role in the suppression of the large-scale vortices associated with highly unstable shear layers and driven by RM instability.…”
Section: Viscosity Effectsmentioning
confidence: 99%